1966
DOI: 10.1021/bi00870a004
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Aldosterone Biosynthesis in Vitro*

Abstract: Biosynthesis of 18-hydroxycorticosterone and aldosterone from corticosterone by bovine, guinea pig, and particularly sheep adrenal tissue has been studied. Both "18-hydroxylase" and "18-ol-dehydrogenase" were located mainly in the mitochondrial fraction.Reduced triphosphopyridine nucleotide (TPNH)and not reduced diphosphopyridine nucleotide (DPNH) was the cofactor for C-18 hydroxylation; presence of oxidized triphosphopyridine (TPN+) or diphosphopyridine nucleotide (DPN +) in the incubation media resulted in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

1967
1967
1994
1994

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 63 publications
0
9
0
1
Order By: Relevance
“…The only step that is unique in the biosynthesis is the conversion of corticosterone to aldosterone, which occurs in the mitochondrial fraction (7)(8)(9). The steps involved are presumably corticosterone --18-hydroxycorticosterone --aldosterone.…”
Section: Introductionmentioning
confidence: 99%
“…The only step that is unique in the biosynthesis is the conversion of corticosterone to aldosterone, which occurs in the mitochondrial fraction (7)(8)(9). The steps involved are presumably corticosterone --18-hydroxycorticosterone --aldosterone.…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition by metyrapone of the 18-hydroxylation of DOC in man has been shown by Shoneshofer et al (16), and the inhibition of the 18-hydroxylation of B in vitro has been reported by several authors (17)(18)(19)(20). In some of these studies, 18-hydroxylation is reported to be more sensitive than ll/?-hydroxylation to the action of metyrapone (19)(20)(21).…”
Section: Discussionmentioning
confidence: 83%
“…Der Einflu$ von Magnesium auf die Mineralocorticoidproduktion der Nebenniere ist nut wenig untersueht, obgleich bioehemisehe Befunde [14,15] Ver/~nderungen der Aldosteronsekretion ohne gleichartige VerKndenmgen der Cortieosteronsekretion spreehen ffir einen Einflu$ des Magnesiums auf einen sp/iten Syntheseschritt des Aldosterons. Bemerkenswert ist in diesem Zusammenhang eine mehrfaeh zu beobaehtende Ubereinstimmung der Magnesiumwirkung mit der yon Heparin: Eine erhShte Heparinkonzentration ffihrt an der Nebenniere nut in vivo, nicht in vitro zu einer isolierten Verminderung der Aldosteronsekretion durch Blockade eines sp/~ten Synthesesehritts yore Corticosteron zum Aldosteron (Cejka u.…”
Section: Diskussionunclassified